Studi Analisis Pembelajaran Abad 21 di MA Mu’allimin Mu’allimat Rembang Berbasis Pesantren - Taufiqurrahman, Moh Faiz; Sudiyono, Sudiyono; Khasanah, Irma Nur; Ma’ali, Izzul; Baarizi, Muhammad (AL-BURHAN, 2024)
Since the existence of 21st century learning, teachers and students are required to be able to apply the 4c skills, namely critical thinking, communication, collaborative and creative, and not only that, digital-based learning is also needed to support learning so that it does not appear monotonous, therefore researchers are interested in finding out what the 21st century learning process is like at the MA Mu'allimin M'allimat Rembang school which is based on Islamic boarding schools. This research uses a descriptive qualitative research method, the data collection methods used interview, observation and documentation methods, while the data sources used in this research are primary data sources are school principals, head of curriculum, guidance teachers and several students MA Muallimin Muallimat Rembang and secondary data in the form of internet, archives, magazines, educational books. The results of this research show that 21st Century Learning at the Islamic Boarding School-based Madrasah Mu'allimin Mu'allimat Rembang shows that there is still a lack of implementation of 21st century learning due to several reasons, namely two main issues that influence the learning process at the madrasa. The first issue is the limited number of learning hours which must be adjusted to the Islamic boarding school's schedule. The second issue is the lack of teacher professional development.Keywords :  Analysis Study, Century Learning 21 st, Islamic Boarding School.